Un Homiliari i una col·lecció homilètica carolingis, copiats a l'entorn de l'any 900 (Vic, Arx. Cap., ms. 60, i Arx. Episc., frag. XXIII/27) - Altés i Aguiló, Francesc Xavier (Miscel·lània litúrgica catalana, 2012)
The wide diffusion and the influence that the Carolingian homiletical literature had in the dioceses of the Marca Hispanica has a new proof with tho works until now unknown, that had been probably copied around 900 in the scriptoria of the city of Narbonnese ecclesiastical province. They are a new Carolingian homiliary (Vic, Arxiu Capitular, ms. 60) and a fragment from a Carolingian homiletical collection (Vic, Arxiu Episcopal, Fragments, XXXIII/27), that we find assumed and reflected in the Catalan codicological tradition.